Varjenje polizdelkov za nadaljnjo obdelavo - tehnologija prihodnosti v avtomobilski industriji - Tušek, Janez (Strojniški vestnik, 1999)
This paper deals with the welding of tailored blanks (semi-products), which are further treated or formed after welding to obtain a final semi-product or product. Some characteristic examples of tailor welded blanks and some characteristic automobile parts which may be welded from variously shaped plates having different thicknesses and made of different materials are shown schematically. Two groups of welding processes suitable for the welding of tailored blanks are described from the technical and economic point of view. The first is fusion welding, typically represented by laser welding, and the second is cold pressure welding. Different processes which may be used for the welding of tailored blanks are described. A practical example of welding of tailored blanks made of different materials is shown.
Keywords: automotive industry; avtomobilska industrija; pločevina; talilno varjenje; lastnosti